2016
DOI: 10.1155/2016/9478204
|View full text |Cite
|
Sign up to set email alerts
|

Timing of Caffeine Therapy and Neonatal Outcomes in Preterm Infants: A Retrospective Study

Abstract: Background. Caffeine is widely used to treat apnea of prematurity. Here, we evaluated the efficacy of early caffeine (1-2 DOL) in decreasing the incidence of adverse neonatal outcomes. Methods. A retrospective cohort was used to compare the neonatal morbidity of 150 preterm neonates with gestational age ≤29 weeks. Infants were divided into 3 groups based on the initiation timing of caffeine therapy; (1) early caffeine (1-2 DOL), (2) late caffeine (3–7 DOL), and (3) very late caffeine (≥8 DOL). Results. The neo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 16 publications
0
11
0
Order By: Relevance
“…In a large clinical trial, caffeine has been shown to reduce the rate of BPD in very preterm infants, shortening the duration time of mechanical ventilation and oxygen supplementation [22]. Caffeine appears to be most effective when started within the first few days of life [23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…In a large clinical trial, caffeine has been shown to reduce the rate of BPD in very preterm infants, shortening the duration time of mechanical ventilation and oxygen supplementation [22]. Caffeine appears to be most effective when started within the first few days of life [23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…While there is general consensus that early caffeine administration is associated with a reduction in the rates of death or BPD and patent ductus arteriosus (21), some concerns remain regarding possible adverse effects, such as increased risk of necrotizing enterocolitis (34). Some investigators have called for further randomized clinical trials to examine early versus late therapy, before caffeine prophylaxis can be universally recommended for infants under 29 wk of gestational age (16).…”
mentioning
confidence: 99%
“…This potential benefit of caffeine has been supported by Muhammad et al, Rhein et al and many other authors 17,18 . Similarly CAP trial has clearly demonstrated a reduction in mechanical ventilation by one week by use of caffeine 19 .…”
Section: Discussionmentioning
confidence: 95%